2018
DOI: 10.1017/psrm.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Platforms, Portfolios, Policy: How Audience Costs Affect Social Welfare Policy in Multiparty Cabinets

Abstract: When and why do electoral commitments enhance parties’ ability to implement their preferred policy in multiparty governments? We propose an audience costs theory whereby strong platform commitments enhance parties’ negotiating positions in multiparty cabinets but only when they are on a salient policy issue for core voters and the party controls the policy-relevant portfolio. Utilizing new data on portfolio allocations in eight parliamentary democracies over 40 years, we show that absent a strong platform comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
0
8
0
2
Order By: Relevance
“…Study 1 participants (N = 565) 3 were recruited for this web-based experiment through Qualtrics survey panels, limited to U.S. respondents age 18 or over. Research has shown these panels to be relatively representative of the U.S. population demographically and politically (Boas et al, 2020); however, my analytic sample had a smaller share of White (~65%) and larger share of female (~68%) respondents compared to the 2010 U.S. census (72% and 50.8%, respectively). The modal age category in the sample was 30 to 39 (~43% of sample), and approximately 11% reported working in education (see Table 1).…”
Section: Methodsmentioning
confidence: 75%
“…Study 1 participants (N = 565) 3 were recruited for this web-based experiment through Qualtrics survey panels, limited to U.S. respondents age 18 or over. Research has shown these panels to be relatively representative of the U.S. population demographically and politically (Boas et al, 2020); however, my analytic sample had a smaller share of White (~65%) and larger share of female (~68%) respondents compared to the 2010 U.S. census (72% and 50.8%, respectively). The modal age category in the sample was 30 to 39 (~43% of sample), and approximately 11% reported working in education (see Table 1).…”
Section: Methodsmentioning
confidence: 75%
“…A third research avenue is gauging the effect of shifts in political power on welfare generosity and the nature of policy change (Alexiadou & Hoepfner, 2019; Häusermann et al, 2013). Despite evidence of the marked decline in the importance of traditional left partisanship (Stephens, 2015), several studies suggest that partisanship of the government does still matter (Allan & Scruggs, 2004; Amable et al, 2006; Döring & Schwander, 2015; Korpi & Palme, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…3. A recent study by Alexiadou and Hoepfner (2019) show that audience costs affect policy decisions in multiparty cabinets. 4.…”
Section: Supplemental Materialsmentioning
confidence: 99%